Spectrum of Skin Diseases in Pediatric Patients Attending in Pediatric Department in a Tertiary Level Hospital (The Insight, 2024)
Introduction: The skin has a key role in communication of biological functions such as thermoregulation, sensation, and excretion. The skin acts as the interface between oneself and the surroundings, functioning as the primary contact point with the external world. Moreover, it forms a vital barrier against infections and prevents dehydration. However, the impairment of the skin’s normal function can lead to significant morbidity and mortality. Objectives: The aim of this paper was to determine the spectrum of skin diseases in pediatric patients attending in the department of Skin & VD in a tertiary level hospital. Methods: This was a descriptive type of cross-sectional study conducted at the Department of Skin & VD in Mugda Medical College, Dhaka, Bangladesh, during January, 2023 to December, 2023.Results: A total of 100 OPD pediatric patients with skin disorders aged (1-15) years were enrolled in this study.   The most frequent infective skin disease was scabies which was 41(47.67%) followed T inea corporis 19(22.09%), Tinea capitis 9(10.47%),Pityriasis versicolor 6(6.98%), Carbuncles/furuncles 33.48%), Pityriasis rosea 2(2.33%) and Bullous impetigo and Tinea pedis followed the same 2(2.33%), Varicella 1(1.16%) and Candidiasis followed the same 1(1.16%).The most frequent skin  non-infective skin  disease was observed Atopic dermatitis which was 4(28.57%) followed Papular urticarial 3(21.44%), Acne 2(14.29) and Alopecia followed the same 2(4.29%), Seborrheic  dermatitis 1(7.14%) and , Miliaria, Tuberous sclerosis followed the same 1(7.14%). Conclusion: This study investigated that 86% of the study children suffered from infective skin diseases which included scabies, T inea corporis , Tinea capitis , Pityriasis versicolor, Carbuncles/furuncles, Pityriasis rosea  ,Bullous impetigo ,Tinea pedis , Varicella , Candidiasis and 14% children suffered from non-infective skin diseases which included Seborrheic dermatitis, Papular urticarial,  Alppecia, Atopic dermatitis,  Miliaria, Tuberous sclerosis which are responsible for children morbidity and mortality in Bangladesh.
Keywords: Patients; pediatric; skin; spectrum; diseases